2018
DOI: 10.1177/1359105317751616
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of representational and behavioral hyperactivity in patients with fibromyalgia syndrome

Abstract: Fibromyalgia is associated with a premorbid hyperactivity. This study examines how contextual and personality factors contribute to premorbid hyperactivity. A total of 45 patients completed questionnaires. The results show that the number of children and the basic bodily needs neglect (and their interaction) explain nearly 50 percent of the variance of hyperactivity. The neglect toward bodily needs completely mediates the relation between self-oriented perfectionism and hyperactivity. This study sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Our work did not gather personality trait information, so it is not clear whether participants describing having pushed themselves reflected perfectionism or simply work pressures. However, a recent study by Grisart et al (2018) found a positive link between self-oriented perfectionism and hyperactivity, mediated by neglect of bodily needs, in their sample of 45 women with fibromyalgia. Thus, fibromyalgia may be precipitated in vulnerable individuals by heavy demands, high self-imposed expectations, and self-neglect in meeting those demands and expectations.…”
Section: Discussionmentioning
confidence: 86%
“…Our work did not gather personality trait information, so it is not clear whether participants describing having pushed themselves reflected perfectionism or simply work pressures. However, a recent study by Grisart et al (2018) found a positive link between self-oriented perfectionism and hyperactivity, mediated by neglect of bodily needs, in their sample of 45 women with fibromyalgia. Thus, fibromyalgia may be precipitated in vulnerable individuals by heavy demands, high self-imposed expectations, and self-neglect in meeting those demands and expectations.…”
Section: Discussionmentioning
confidence: 86%
“…Insufficient adaptation to stressors, increased catastrophizing, and poor coping skills prevail in pain patients [77]. Maladaptive coping strategies lead to deficient stress response to changes in the reactivity of the HPA axis and autonomic nervous system [78] Patients with FM show an abnormal underactive stress reactivity involving the hypothalamic-pituitary axis (HPA) [79]. Inconsistent results regarding the HPA axis abnormalities in FM exist in the literature (decreased or normal urinary free cortisol, loss of diurnal cortisol fluctuation, and elevated evening cortisol levels).…”
Section: Personality Biomarker Related To Physical Activity Status In Fmmentioning
confidence: 99%
“…The primary method for helping patients to do things that ‘fly under the radar’ of their body’s stop signals, is to help them learn how to pay attention to their bodies in more intuitive and compassionate way. A key component of the Body Reprogramming approach is the targeting of premorbid hyperactivity and self-orientated perfectionism, particularly relating to ongoing heavy demands and high self-imposed expectations which often result in neglect of bodily needs ( Grisart et al, 2018 ).…”
Section: Principles Incorporated Within Body Reprogrammingmentioning
confidence: 99%